Controversy and Arguments for The Application of Rasm 'Utsmānī On The Mushaf of The Qur'an - Sopyan Hadi; Rifanto Bin Ridwan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This paper presents information about the orthography controversy of the muṣḥaf that was written and compiled during the time of Caliph ‘Uthmān ibn ‘Affān, also known as the rasm ‘uthmānī, due to the political intervention in the process of codification. The script style of Rasm ‘uthmānī represents a cultural heritage of early Arabic writing closely linked to the generation of the Prophet’s companions. During the early period of its promulgation, many non-Arab Muslims struggled with correctly reading the muṣḥaf. As a result, the ‘uthmānī mushaf underwent improvements incorporating standardised Arabic writing rules and ultimately became the global standard for Muslims. This paper also addresses the arguments supporting the policy of implementing Rasm ‘uthmānī in the writing of the muṣḥaf al-Qur'an. The method used in this research is in the form qualitative descriptive analytical research, namely research that seeks to provide a complete picture as well as explore in depth the aspect that have relevance to the controversy of the rasm ‘utsmānī which is a literature study, where data or data sources are taken based on and classical books,  books, and articles.